Strategic marketing in fragile economic conditions - Samanta, Irene, 1956-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2014)
"This book provides relevant theoretical frameworks and the latest empirical research findings relating to consumer confidence, marketing strategies, and the influence of trust during a time of economic crisis"--Provided by publisher.
Loyalty in crisis: evidence from Greece / Ilias P. Vlachos, Dimitra Skoumpopoulou -- The evolution of trust in Japan: the case of vertical Keiretsu groups / Nabyla Daidj -- Trust deficit in public sector: causes, consequences, and strategies to mitigate / Vedantam Leela -- Customers' satisfaction and loyalty in the economic recession: the case of a Greek bank / Irene Samanta -- Sustainable competitive advantage in turbulent business environments using critical organizational capabilities and resources to manage complexity / Yannis A. Pollalis -- Exploring the relationship between the eco-labels and green buying behaviour with reference to Mumbai City / Ritu Sinha -- Towards leadership marketing: an exploratory and empirical study / Wilson Ozuem, Alina O'Keeffe -- The impact of marketing strategy in small family businesses / Anastasios Ntanos, Stamatios Ntanos -- The role of brand management in emerging markets / Kijpokin Kasemsap -- The antecedents of word-of-mouth behaviour: the service quality perspective / Ho Yin Wong, Anthony Perrone -- How is internal marketing understood?: an examination of stakeholder perspective / Wilson Ozuem, Natalie Limb -- Growing e-marketing trends in India / Laxhminarayan Das -- Tourism promotion through web / Nilanjan Ray, Dillip Kumar Das, Somnath Chaudhuri -- The effect of e-business in B2B relationships / Irene Samanta, Nondas Pitticas -- Electrotextiles: a novel product for the textile industry / Georgios Priniotakis.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 09/19/2014).
Keywords: Marketing -- Management; Consumer confidence; Financial crises; Economic downturn; Market performance; Strategic marketing; Trust models; Value creation in a network economy; Electronic books